Selective oxidation of cyclohexane in supercritical carbon dioxide - Kerry Yu, K; Abutaki, A; Zhou, Y; Yue, B; He, H; Tsang, S (2007)
A feasibility study into the novel concept of using molecular oxygen to carry out one-step catalytic oxidation of cyclohexane to adipic acid in supercritical carbon dioxide over two types of catalysts, namely Co 2+/Mn2+/NaBr and Ag polyoxometallate, the silver decamolybdodivanadophosphate (Ag5PMo10V2O 40) was carried out. Poor activity and selectivity towards adipic acid were initially noted over the aqueous micellar Co2+/Mn 2+/NaBr catalyst for the cyclohexane oxidation in supercritical carbon dioxide while under comparable conditions, the same catalyst gave a high activity for alkylaromatics oxidation to corresponding acids. It was later found that the adipic acid, being the extremely polar oxidised products, was virtually insoluble in the supercritical phase, which was rapidly degraded to carbon oxides after its prolonged contact with catalyst and O2. Thus, the one-step cyclohexane oxidation to adipic acid with good selectivity can only be achieved by modifying the solvent with acetic acid or methanol, which enabled isolation of the acid from further oxidation. On the other hand, Ag 5PMo10V2O40 , in methanol modified supercritical carbon dioxide gave an impressive selectivity for cyclohexane conversion to other oxygenates. © Springer Science+Business Media, LLC 2007.